SILENT SIMULATION: THE ABILITY OF GEOGRAPHY EDUCATION STUDENTS TO DO A HORIZONTAL EVACUATION TO A TSUNAMI SAFE ZONE IN PADANG CITY - Nofrion Nofrion; Bayu Wijayanto; Rahmanelli Rahmanelli; Rery Novio; Surtani Surtani; Khairani Khairani; Mohammad Zohir Ahmad (Universitas Negeri Medan, 2021)
This article was written to explain the ability of Geography Education students to do horizontal evacuation to a tsunami safe zone in Padang City and a silent simulation as an alternative of horizontal evacuation. In this research, respondents were asked to do horizontal evacuation in 3 ways, that is walking, power walking and running. The measurement result data were analyzed and compared with the estimated arrival time of tsunami wave in three scenarios based on gender. The results of the research are 1) 47.76 % of respondents did not know the nearest tsunami safe zone from their places; 2) if the earthquake and tsunami scenarios 1 and 2 occurred, the recommended horizontal evacuation technique was running. Silent simulation is a horizontal evacuation simulation carried out independently by residents without waiting for the simulation schedule by the government or related institutions. Silent simulation can be done alone, with family, or with the closest neighbours and combined with daily activities such as marathons or jogging. Through this silent simulation practice, residents can find out the most appropriate evacuation method and the fastest evacuation route to the nearest tsunami safe zone from their respective homes.Keywords: silent simulation, geography education, tsunami safe zone, PadangArtikel ini ditulis untuk menjelaskan kemampuan mahasiswa Pendidikan Geografi dalam melakukan evakuasi horizontal ke zona aman tsunami di Kota Padang dan silent simulation sebagai alternatif evakuasi horizontal. Dalam penelitian ini, responden diminta melakukan evakuasi horizontal dengan 3 cara, yaitu jalan kaki, jalan cepat dan lari. Data hasil pengukuran dianalisis dan dibandingkan dengan perkiraan waktu tiba gelombang tsunami pada tiga skenario berdasarkan jenis kelamin. Hasil penelitian adalah 1) 47,76% responden tidak mengetahui zona aman tsunami terdekat dari tempatnya; 2) jika terjadi gempa bumi dan tsunami skenario 1 dan 2, maka teknik evakuasi horizontal yang direkomendasikan adalah berjalan. silent simulation merupakan simulasi evakuasi horizontal yang dilakukan secara mandiri oleh warga tanpa menunggu jadwal simulasi oleh pemerintah atau instansi terkait. silent simulation bisa dilakukan sendiri, bersama keluarga, atau dengan tetangga terdekat dan dipadukan dengan aktivitas sehari-hari seperti maraton atau jogging. Melalui latihan silent simulation ini, warga dapat mengetahui metode evakuasi yang paling tepat dan jalur evakuasi tercepat menuju zona aman tsunami terdekat dari rumah masing-masing.Kata Kunci: Silent simulation, Pendidikan geografi, Zona aman tsunami, Padang